Financial Literacy in the Projected Curriculum of Australia - Ševčík, Karel (Scientia in educatione, 2017)
The phenomenon of financial literacy has attracted an increasing attention on a global scale. The reason behind this is not only the recent financial crisis but primarily the rising amount of financial problems which affect the lives of individuals. Therefore, there has been an increase in the number of states which implement elements of financial education into their national curricula. Australia also ranks among the countries which have been developing the financial literacy of its students within a specifically tailored school subject. The study focuses on the analysis of financial literacy development within the school curriculum as designed and projected in Australia. The relevant data has been generated via information analysis and it is supposed to support the reflection of the financial literacy concept in the Czech curriculum and offer some inspiration towards future progress. The next aim is to design a categorical system derived from the findings and also from other available studies. The results suggested that financial literacy is also readily understood as an important part of math curriculum, already at the primary levels of education. Authors also acknowledge the approach to different financial issues with regard to content and skills.